2012
DOI: 10.1097/igc.0b013e31826b5dcc
|View full text |Cite
|
Sign up to set email alerts
|

Loss of ARID1A Expression Is an Early Molecular Event in Tumor Progression From Ovarian Endometriotic Cyst to Clear Cell and Endometrioid Carcinoma

Abstract: OBJECTIVES ARID1A is a recently identified tumor suppressor participating in chromatin remodeling. Somatic inactivating mutations of ARID1A and loss of its expression occur most frequently in ovarian clear cell and endometrioid carcinomas and uterine endometrioid carcinomas. Since endometriosis is thought to be a precursor of most ovarian clear cell and endometrioid carcinomas, we undertook an analysis of ARID1A expression of these tumors arising within an endometriotic cyst (endometrioma). MATERIALS/METHODS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
126
2
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 158 publications
(139 citation statements)
references
References 23 publications
7
126
2
4
Order By: Relevance
“…Loss of ARID1A has been suggested as an early molecular event that contributes to tumor development. As an example, the absence of ARID1A immunoreactivity is observed not only in ovarian clear cell and endometrioid carcinomas but also in their adjacent endometriotic cyst epithelium that is contiguous to the carcinoma (52). Because endometriotic cyst epithelium is the cell of origin in many ovarian clear cell and endometrioid carcinomas, future studies should address whether the cyst epithelium with ARID1A loss has higher levels of TERT expression and longer telomere than those cysts with ARID1A retention.…”
Section: Discussionmentioning
confidence: 99%
“…Loss of ARID1A has been suggested as an early molecular event that contributes to tumor development. As an example, the absence of ARID1A immunoreactivity is observed not only in ovarian clear cell and endometrioid carcinomas but also in their adjacent endometriotic cyst epithelium that is contiguous to the carcinoma (52). Because endometriotic cyst epithelium is the cell of origin in many ovarian clear cell and endometrioid carcinomas, future studies should address whether the cyst epithelium with ARID1A loss has higher levels of TERT expression and longer telomere than those cysts with ARID1A retention.…”
Section: Discussionmentioning
confidence: 99%
“…However, previous studies have primarily provided insight into the function of wild-type ARID1A (9,10). Furthermore, in EC, the majority of previous studies have focused on the loss of ARID1A expression as determined by immunohistochemistry or gene sequencing of mutations (7)(8)(9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, in EC, the majority of previous studies have focused on the loss of ARID1A expression as determined by immunohistochemistry or gene sequencing of mutations (7)(8)(9)(10)(11). Therefore, it remains unclear which signaling pathways are influenced by ARID1A mutations and which pathway molecules are targeted by ARID1A mutations in EC pathophysiology.…”
Section: Introductionmentioning
confidence: 99%
“…Alterations of the phosphatidylinositol 3-kinase (PIK3CA)/AKT/mammalian target of rapamycin (mTOR) pathway have been detected in 15%-75% of CCOCs (42)(43)(44)(45)(46)(47)(48)(49) and preclinical data from non-small cell lung cancer have suggested that activation of this pathway correlates with an increased expression of PD-L1 in tumor cells (50).…”
Section: Epithelial Ovarian Cancermentioning
confidence: 99%